THE SOCIOPRAGMATIC ASPECTS OF SPEECH ACTS IN THE ENGLISH AND UZBEK LANGUAGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The current work investigates the sociopragmatic features of speech acts in the English and Uzbek languages. Generally, the article explores the similarities and differences between the use of illocutionary speech acts in these compared languages. The peculiarities of speech acts have been stated with graphics and tables.